2017
DOI: 10.5194/acp-2017-431
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A multi-model approach to monitor emissions of CO<sub>2</sub> and CO from an urban-industrial complex

Abstract: <p><strong>Abstract.</strong> Monitoring urban-industrial emissions is often challenging, because observations are scarce and regional atmospheric transport models are too coarse to represent the high spatiotemporal variability in the resulting concentrations. In this paper we apply a new combination of a Eulerian model (WRF with chemistry) and a Gaussian plume model (OPS). The modelled mixing ratios are compared to observed CO<sub>2</sub> a… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2019
2019
2019
2019

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 51 publications
0
1
0
Order By: Relevance
“…Toja et al [1] demonstrated that the average height of the buildings showed a clear influence on the vertical profile of carbonic oxide concentration. Super et al [2] proposed a multi-model approach based on the combination of Eulerian model and Gaussian plume model to monitor emissions of CO from the urban-industrial complex. For statistical characteristics-based methods, time series analysis and significance test are often used to evaluate air quality.…”
mentioning
confidence: 99%
“…Toja et al [1] demonstrated that the average height of the buildings showed a clear influence on the vertical profile of carbonic oxide concentration. Super et al [2] proposed a multi-model approach based on the combination of Eulerian model and Gaussian plume model to monitor emissions of CO from the urban-industrial complex. For statistical characteristics-based methods, time series analysis and significance test are often used to evaluate air quality.…”
mentioning
confidence: 99%